ANALISIS PENGETAHUAN DOSEN DAN MAHASISWA UNIVERSITAS BHAYANGKARA JAKARTA RAYA TENTANG PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL - Yudhawasthi, Ciwuk Musiana; Rifaldi Akbar, Moh.; Dwi Lestari, Anita; Nabawiyah, Dinda; Faustina, Helena (JURNAL SIPAKALEBBI, 2023)
Cases of sexual violence are quite common in the higher education environment. In early 2023, as part of the implementation of Permendikbudristek No. 30 of 2021, which is also a "mandatory" program in all tertiary institutions in Indonesia, the University of Bhayangkara Jakarta Raya (Ubharajaya) has formed a Task Force for the Prevention and Handling of Sexual Violence (Satgas PPKS). In order to formulate the right program to create Kampus Merdeka from Sexual Violence, the PPKS Task Force needs to know in advance how far the Ubharajaya academic community knows and understands about sexual violence in their campus environment. Because of that, research was conducted on the knowledge of Ubharajaya academics regarding sexual violence. This type of research is quantitative using a descriptive method with a population of all Ubharajaya lecturers and students from 7 faculties on the Ubharajaya Campus, Summarecon Bekasi, who are still actively teaching and learning in 2023. From this population, 310 samples were taken, consisting of 29 lecturers and 281 students, through stratification techniques. Data collection was carried out by distributing questionnaires made in Google Forms, which can be accessed through the WhatsApp (WA) application. The results of the study show that Ubharajaya academics in general have relatively good knowledge about sexual violence as well as its forms and methods of prevention. However, when studied in more depth based on the gender, profession, and faculty of origin of the respondents, there are interesting findings that need to be followed up in more comprehensive and integrative research.